Oligometastasis in breast cancer—current status and treatment options from a radiation oncology perspective - Piroth, Marc D.; Krug, David; Feyer, Petra; Baumann, Rene; Combs, Stephanie; Duma, Marciana-Nona; Dunst, Juergen; Fastner, Gerd; Fietkau, Rainer; Guckenberger, Matthias; Haase, Wulf; Harms, Wolfgang; et al. (Strahlentherapie und Onkologie, 2022)
Evidence from a few small randomized trials and retrospective cohorts mostly including various tumor entities indicates a prolongation of disease free survival (DFS) and overall survival (OS) from local ablative therapies in oligometastatic disease (OMD). However, it is still unclear which patients benefit most from this approach. We give an overview of the several aspects of stereotactic body radiotherapy (SBRT) in extracranial OMD in breast cancer from a radiation oncology perspective. A PubMed search referring to this was conducted. An attempt was made to relate the therapeutic efficacy of SBRT to various prognostic factors. Data from approximately 500 breast cancer patients treated with SBRT for OMD in mostly in small cohort studies have been published, consistently indicating high local tumor control rates and favorable progression-free (PFS) and overall survival (OS). Predictors for a good prognosis after SBRT are favorable biological subtype (hormone receptor positive, HER2 negative), solitary metastasis, bone-only metastasis, and long metastasis-free interval. However, definitive proof that SBRT in OMD breast cancer prolongs DFS or OS is lacking, since, with the exception of one small randomized trial (n = 22 in the SBRT arm), none of the cohort studies had an adequate control group. Further studies are needed to prove the benefit of SBRT in OMD breast cancer and to define adequate selection criteria. Currently, the use of local ablative SBRT should always be discussed in a multidisciplinary tumor board.
CRIS-Team Scopus Importer:2022-05-20
Keywords: Breast cancer; Oligometastases; OMD; Radiotherapy; Stereotactic body radiotherapy